Atmospheric microfibers dominated by natural and regenerated cellulosic fibers: Explanations from the textile engineering perspective. (15th January 2023) - Liu, Jianli; Zhu, Bo; An, Lihui; Ding, Jiannan; Xu, Yuyao
Abstract: A large number of synthetic fibers found in the environment have aroused public conern about microfiber pollution. However, more studies have found that the number of natural fibers and regenerated cellulose fibers in the environment is much higher than that of synthetic fibers. If humans are exposed to excessive amounts of these two types of fibers for a long time, they may also suffer physiological injury. However, this is often ignored by previous research on microfiber pollution. Recently, some publications attributed the dominating amounts of natural fiber and regenerated cellulosic fibers in the environment to the past yield advantage and low durability compared to synthetic fibers. This correspondence supports that view and further discusses the main reasons for the domination of natural and regenerated cellulosic fibers: their physicochemical properties, material sources, manufacturing processes (staple yarn and filament) and applications. This correspondence aims to arouse attention to the potential impact of natural fibers and regenerated cellulose fibers. Graphical abstract: Image 1 Highlights: Natural and regenerated cellulosic fibers dominate atmospheric microfibers. Airborne microfiber pollution is explained from the textile engineering perspective. Long-term and high exposure to microfiber results in health risks.